2018
DOI: 10.1007/s11244-018-1103-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Induced Effect of Potassium on the Reactivity of Vanadate Species in V2O5–WO3/TiO2 SCR-Catalyst

Abstract: A renewed interest of benchmark V2O5/WO3/TiO2 SCR-catalysts is discernible for the depollution of stationary sources jointly with the use of bio-fuels as substitute to fossil fuels. However, the resistance to deactivation has to be reconsidered according to additional alkaline contamination. This study tried to elucidate the impact of potassium on the stability of vanadate and tungstate species at various dispersions for two different K/V ratios equal to 0.2 and 0.8. Different kinetic behaviors of fresh and K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…A detailed kinetic analysis reveals that NH 3 adsorption/desorption, NH 3 oxidation and DeNO x activity are all affected by K poisoning. Similar tendencies were demonstrated by Siaka et al [162], who claim that potassium preferentially neutralizes strong acid sites and alters V=O redox sites, leading to stabilization of well-dispersed VO x species. Contrasting with the results of Xie et al, Chen et al concluded that tungsten oxide can serve as a sacrificial agent protecting vanadia from severe K poisoning [163].…”
Section: Potassium and Calcium Poisoningsupporting
confidence: 84%
“…A detailed kinetic analysis reveals that NH 3 adsorption/desorption, NH 3 oxidation and DeNO x activity are all affected by K poisoning. Similar tendencies were demonstrated by Siaka et al [162], who claim that potassium preferentially neutralizes strong acid sites and alters V=O redox sites, leading to stabilization of well-dispersed VO x species. Contrasting with the results of Xie et al, Chen et al concluded that tungsten oxide can serve as a sacrificial agent protecting vanadia from severe K poisoning [163].…”
Section: Potassium and Calcium Poisoningsupporting
confidence: 84%
“…Four peaks at 146, 396, 515, and 638 cm –1 were detected on the surface of all catalysts and were attributed to anatase TiO 2 , , which indicated that the structure of TiO 2 was not changed by the added K salt. The spectral peaks at 1013 cm –1 and 900–1000 cm –1 detected on the surface of the fresh catalyst were attributed to VO groups of monomeric and polymeric vanadyl species, respectively. , Generally, the monomeric vanadyl species exist predominantly on the TiO 2 surface by coverage of the basic sites with Ti–O–V . The peak at 1013 cm –1 was not detected on the K-poisoned catalysts, which meant that the monomeric VO groups may combine with the added K + or anion to generate V–O–K or V–O–e – .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The spectral peaks at 1013 cm −1 and 900−1000 cm −1 detected on the surface of the fresh catalyst were attributed to V�O groups of monomeric and polymeric vanadyl species, respectively. 28,29 Generally, the monomeric vanadyl species exist predominantly on the TiO 2 surface by coverage of the basic sites with Ti−O−V. 30 The peak at 1013 cm −1 was not detected on the K-poisoned catalysts, which meant that the monomeric V�O groups may combine with the added K + or anion to generate V−O−K or V−O−e − .…”
Section: Textural Propertiesmentioning
confidence: 99%
“…At present, the commonly used NOx removal technology is selective catalytic reduction (SCR) [4][5][6][7] The widely used commercial V 2 O 5 -WO 3 (MoO 3 )/TiO 2 catalyst has some disadvantages, such as the toxicity of V 2 O 5 , high price and narrow reaction temperature ranges (300-400 1C). [8][9][10] Therefore, the design of a novel, non-toxic and low-cost denitration catalyst has attracted much attention, which can enhance the catalytic activity and widen the reaction temperature range.…”
Section: Introductionmentioning
confidence: 99%